2006 International Conference of the IEEE Engineering in Medicine and Biology Society 2006
DOI: 10.1109/iembs.2006.260478
|View full text |Cite
|
Sign up to set email alerts
|

Feature Extraction & Lips Posture Detection Oriented to the Treatment of CLP Children

Abstract: Adequate recognition of lips posture for speech articulation analysis requires of the measurement of several anthropometric mouth parameters. These are needed to estimate the position and contour of the lips and teeth and tongue positions, as well. Here, a method is proposed for lips contour detection under natural conditions without any extra hardware requirements for image acquisition. The purpose of the suggested process is to obtain the lips contour based on red hue fields detection. Afterward, geometrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Embora a natureza do processo neurodegenerativo verificado na DP não seja conhecida, atualmente tem sido sugerido o envolvimento do alto potencial oxidativo da dopamina (DA) na geração de H 2 O 2 e outras ERO [29], assim como à alta concentração de ferro e sua homeostase alterada [30], e baixos níveis de glutationa [31]. O metabolismo alterado do ferro nas suas formas transicional ferrosa (Fe +2 ) e férrica (Fe +3 ) tem forte potencial oxidante pela geração de radicais hidroxil (OH • ) com H 2 O 2 através da reação de Fenton/Haber-Weiss [32].…”
Section: Estresse Oxidativo E Doença De Parkinsonunclassified
“…Embora a natureza do processo neurodegenerativo verificado na DP não seja conhecida, atualmente tem sido sugerido o envolvimento do alto potencial oxidativo da dopamina (DA) na geração de H 2 O 2 e outras ERO [29], assim como à alta concentração de ferro e sua homeostase alterada [30], e baixos níveis de glutationa [31]. O metabolismo alterado do ferro nas suas formas transicional ferrosa (Fe +2 ) e férrica (Fe +3 ) tem forte potencial oxidante pela geração de radicais hidroxil (OH • ) com H 2 O 2 através da reação de Fenton/Haber-Weiss [32].…”
Section: Estresse Oxidativo E Doença De Parkinsonunclassified
“…Step 1: Divide the judges into two groups: (1) doctors and (2) laymen and then perform Kendall's (W) procedure to these groups respectively whose result is listed in Table 5. It can be seen that the consistency for the group of five laymen (0.925) is a little better than the doctor's (0.835).…”
Section: Kendall's (W) Testmentioning
confidence: 99%
“…In [23] and [24], HMM based visual speech recognition is described. Several studies have found that a multimodal approach to speech recognition, combining speech, mouth and face features, gives significantly improved performance over a single mode approach under trying test conditions [1], [3], [25] and [26].…”
Section: A Related Workmentioning
confidence: 99%